Pendampingan Teknis Pengelolaan Kondensat untuk Meningkatkan Keamanan dan Kebersihan Lingkungan di PLTMG Bangkanai - Moh. Syaiful Anwar; Feby Salma Ayu Safitri; Mochamad Shaleh (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
Condensate produced in PLTMG operations may create puddles, reduce workplace cleanliness, and increase accident risks if not properly managed. This community service activity aimed to improve workers’ understanding of condensate management to support safety and environmental cleanliness at PLTMG Bangkanai. The program was conducted on 15–16 April 2026 involving 10 workers. The implementation method consisted of four stages: preparation, material delivery, field assistance, and evaluation. The training focused on understanding condensate hazards and safe handling procedures, while field assistance ensured proper implementation in the operational area. The results showed improved worker awareness in area inspection, puddle handling, and reporting coordination. Overall, the activity positively enhanced workers’ understanding and behavior in maintaining a safer and cleaner operational environment